Evaluasi kepuasan kerja perawat di ruang MPKP, persiapan mpkp dan non MPKP - Ibrahim Rahmat; Maulina Nugraheni; Sri Werdati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: This study aims to determine differences in job satisfactionof nurses in three rooms with a nursing care delivery system by themethod of PNPM, Preparation and non PNPM PNPM GrhasiaHospital Yogyakarta. The method used was a cross sectional studywith comparative descriptive approach. The results show that nursesat PNPM is largely at the level of job satisfaction is high (77.78%).Meanwhile, in the preparation of non-PNPM PNPM and 100% ofnurses are in high satisfaction rates. The statistical results showed nodifference in job satisfaction between PNPM, PNPM preparation,and non PNPM.